Evaluation of potential reproductive seasonality in brown brocket deer (Mazama gouazoubira) bucks - Tanaka, Yuki [UNESP]; Herédias-Ribas, Cláudia Maria [UNESP]; Baldini, Maria Helena Mazzoni [UNESP]; Guevara, José Eduard Hernández [UNESP]; Duarte, José Maurício Barbanti [UNESP] (Elsevier, 2021)
Photoperiod is the main cue that controls seasonal reproduction in deer from temperate regions, like secretion of testosterone by the testis, neck enlargement, and testis development. However, little is known about its effect on the reproduction of tropical deer species. This research aimed to assess the potential seasonality of the brown brocket deer (Mazama gouazoubira) by melatonin treatment. Reproductive parameters such as testicular volume, neck circumference, and semen quality were evaluated from day 0 to 90, and fecal androgen metabolites (FAM) from day −28 to 91. Melatonin treatment was administered from day 0 to 60. In total, seven individuals were used in the study. Four animals were allocated to the treated group (TG) and three to the control group (CG). The neck circumference and some seminal parameters did not show a significant difference between CG and TG and along the experimental period. High FAM levels were observed for the TG on days 7, 14, 21, 35, 84, and 91 (p < 0.05). The mean testicular volume was reduced from day 0 to 30 (p < 0.05) and from day 0 to 90 (p < 0.05), with no increase in the mean testicular volume from day 30 to 60 (p > 0.05). Sperm motility was the highest on day 60 compared with day 0 (p < 0.05). Although not statistically different, membrane integrity and major defects tended to be higher and lower, respectively, in the TG compared with the CG. For these parameters, the incremental change (%) per individual showed that males from the TG tended to have a higher percentage during the melatonin treatment, hence melatonin might affect these seminal characteristics. These findings suggest that exogenous melatonin might enhance FAM levels and sperm motility.
Keywords: Fecal androgen metabolites; Melatonin; Neotropical deer; Seasonality; Semen